2023
DOI: 10.1057/s41599-023-02458-4
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia use and its impact on the effectiveness of educators: a technology acceptance model perspective

Xuan Tang,
Siti Rohaida Binti Mohamed Zainal,
Quan Li

Abstract: Amidst the contemporary shifts within early childhood education (ECE) in China, the significance of multimedia tools and their effective deployment by educators is increasingly paramount. Situated within the theoretical underpinnings of the Technology Acceptance Model (TAM), this inquiry elucidates the intricate dynamics between the Perceived Usefulness (PU) and Perceived Ease of Use (PEU) of said tools and their consequential influence on educators’ effectiveness. Empirical data gleaned from a rigorous quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…This study references the research conducted by Scherer et al (2019), Granić andMarangunic (2019), andTang et al (2023) in applying the TAM to evaluate the uptake of contemporary technology by educators and students. The TAM components, PU and PEOU, are essential for comprehending instructors' and students' readiness to use virtual reality for teaching and learning about oil paintings.…”
Section: Application Of Tam In This Studymentioning
confidence: 98%
See 1 more Smart Citation
“…This study references the research conducted by Scherer et al (2019), Granić andMarangunic (2019), andTang et al (2023) in applying the TAM to evaluate the uptake of contemporary technology by educators and students. The TAM components, PU and PEOU, are essential for comprehending instructors' and students' readiness to use virtual reality for teaching and learning about oil paintings.…”
Section: Application Of Tam In This Studymentioning
confidence: 98%
“…The researchers determined that the TAM was suitable for predicting the adoption of technology in a preschool educational setting because of its focus on usage intention and fostering favourable attitudes toward technology. Tang et al (2023) employed TAM to investigate how multimedia tools impact early childhood education and to evaluate the influence of multimedia tool integration on educational efficacy. The researchers emphasised the significant impact of instructors' perceptions of the utility and simplicity of using multimedia technologies.…”
Section: Tam In Educational Settingsmentioning
confidence: 99%
“…These curricula equip students with the skills required for a multicultural world, emphasising intercultural competence. Additionally, Tang et al (2023) reported that in Guangdong, China, educators' effectiveness is enhanced by the use of multimedia in educational activities, indicating the positive impact of technology integration in multicultural educational settings. Incorporating technology can further enhance access to inclusive education, a key component of SDG 4, by broadening learning opportunities and making education more accessible to diverse student populations.…”
Section: Multicultural Education and Curriculum Developmentmentioning
confidence: 99%